2021
DOI: 10.1002/cbic.202100240
|View full text |Cite
|
Sign up to set email alerts
|

Core Steps to the Azaphilone Family of Fungal Natural Products

Abstract: Azaphilones are a family of polyketide‐based fungal natural products that exhibit interesting and useful bioactivities. This minireview explores the literature on various characterised azaphilone biosynthetic pathways, which allows for a proposed consensus scheme for the production of the core azaphilone structure, as well as identifying early diversification steps during azaphilone biosynthesis. A consensus understanding of the core enzymatic steps towards a particular family of fungal natural products can ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Trans -acting hydrolases with similar proof-reading activities have been identified in the biosynthesis of lovastatin 1, 133 asperfuranone 19 , 69 azanigerone 80 , 154 and various Monascus azaphilone-derived pigments. 155 Similar roles for cis -acting TE domains have been characterized in NRPKS such as PksA involved in the biosynthesis of 10 . 156,157…”
Section: Pks Requiring Collaborating Enzymes For Polyketide Releasementioning
confidence: 80%
“…Trans -acting hydrolases with similar proof-reading activities have been identified in the biosynthesis of lovastatin 1, 133 asperfuranone 19 , 69 azanigerone 80 , 154 and various Monascus azaphilone-derived pigments. 155 Similar roles for cis -acting TE domains have been characterized in NRPKS such as PksA involved in the biosynthesis of 10 . 156,157…”
Section: Pks Requiring Collaborating Enzymes For Polyketide Releasementioning
confidence: 80%
“…The enzyme CazM, a nonreducing polyketide synthase involved in chaetoviridin synthesis, is the closest homolog (67% identity, 78% similarity) to Psc_Aza_B 52 . Other azaphilone biosynthetic pathways involving both highly reducing and nonreducing polyketide synthases are described in the literature 47 , 53 . A synteny cluster comparison using clinker 50 revealed that the polyketide synthase pair involved in other azaphilone biosynthetic pathways (i.e., chaetoviridin, asperfuranone, azanigerone, mitorubrinol and ankaflavin) is conserved and homologous to Psc_Aza_A and Psc_AzaB (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…2021), but because of potential toxicity they might not be suited in many applications as well. Some other azaphilones may also possess quinone-like properties, potentially applicable to some or more of the applications mentioned in this review (Pavesi et al, 2021;Williams et al, 2021).…”
Section: Quinone Methidesmentioning
confidence: 99%